Fatigue determination of the kenaf/PLA composite structure using fatigue specimen (ASTM D7791): a computational analysis - Abbu, Muthana Adil Najim; Hashim, Doaa Talib; Albegmprli, Hasan Mohammed Ahmed; Mezaal, Mustafa Ridha (Eastern-European Journal of Enterprise Technologies, 2023)
In this investigation, a kenaf/PLA composite specimen was subjected to the fatigue load, and the results were analyzed numerically. Some of the most significant fatigue tool aspects that were looked into were life expectancy, damage, alternative stress, and biaxiality indication. The static structural tool was utilized in order to predict the numerical analysis, and the calculations were performed with the GoodMan theory of fatigue. The loading was completely reversed so that it was equal to 30 kN. When it was discovered that the system could continue to function even after 1e6 cycles had been completed. After applying the alternative load of 30 kN, the biaxiality indication was found to be 0.425, with a minimum value of 0.9. It has been determined how much damage has occurred. The minimum amount of cycles necessary to reach the maximum damage potential is 1000, while the maximum amount of cycles necessary to reach the maximum damage potential is 1.7662·106. It has been established that there is another stress that is comparable to this one. Based on the findings of the investigation, it was determined that the fillet regions of the specimen were subjected to a maximum alternative stress of 716.4 MPa. The alternative stress cannot drop below 31.276 MPa under any circumstances. It has been determined that 106cycles have been spent living in total by the calculation. It has been found out that there is not going to be any damage regardless of the number of cycles that pass due to the fact that that number is 1. It was found that the alternative stress could reach a maximum value of 716.4 MPa, so that was the value that was used for the alternative stress